Improving single-cell transcriptome sequencing efficiency with a microfluidic phase-switch device. Issue 24 (5th November 2019) - Zhang, Baoyue; Xu, Hong; Huang, Yuqing; Shu, Weiliang; Feng, Hongtao; Cai, Jin; Zhong, Jiang F.; Chen, Yan
Abstract : In this paper, we present a novel method to improve the efficiency of single-cell transcriptome sequencing for analyzing valuable cell samples. Abstract : In this paper, we present a novel method to improve the efficiency of single-cell transcriptome sequencing for analyzing valuable cell samples. The microfluidic device we designed integrates multiple single-cell isolation chambers with hydrodynamic traps and achieves a nearly 100% single-cell capture rate and minimal cell loss, making it particularly suitable for samples with limited numbers of cells. Single cells were encapsulated using a novel phase-switch method into picoliter-sized hydrogel droplets and easily recovered for subsequent reactions. Minimizing the reaction volume resulted in a high reverse transcription (RT) efficiency for RNA sequencing (RNA-Seq). With this novel microfluidic platform, we captured dozens of hESCs (H9) simultaneously and obtained live cells in individual picoliter volumes, thus allowing for the convenient construction of a high-quality library for deep single-cell RNA-Seq. Our single-cell RNA-Seq results confirmed that a spectrum of pluripotency existed within an H9 colony. This integrated microfluidic platform can be applied to various cell types for the investigation of rare cellular events, and the phase-switch single-cell processing strategy will improve the efficiency and accessibility of single-cell transcriptome sequencing analysis.